The Influence of Social Support and Family Interaction on Marital Quality in Middle-Aged Families - Fadhila Dinda Haliza; Tin Herawati (Journal of Child, Family, and Consumer Studies, 2025)
Middle-aged families represent a transitional stage in which the youngest child leaves the parental home and couples begin to enter retirement age. This stage often gives rise to emotional challenges, such as empty nest syndrome, which may affect marital quality. This study aimed to analyze the influence of social support and family interaction on marital quality among middle-aged families. A cross-sectional design was employed, involving 32 wives as respondents who were still living with their husbands while all children had already lived separately. The study was conducted in Gunung Batu Subdistrict, West Bogor District. Data were collected using structured questionnaires and analyzed through descriptive statistics, Pearson correlation, and multiple linear regression. The findings show that social support and family interaction were generally at moderate levels. Support from the nuclear family was high, whereas support from extended family and neighbors was low. Marital quality was mostly low, particularly in the happiness dimension, although satisfaction tended to be higher. Regression analysis showed that husband–wife interaction had a significant positive effect on marital quality, whereas parent–child interaction had a significant negative effect. These findings underscore the importance of strengthening family interactions to support marital quality in middle-aged families